UKURAN ANTROPOMETRI GIZI YANG BERHUBUNGAN DENGAN PREDIABETES PADA OBESITAS DI PEJAGALAN, JAKARTA (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2018)
Prevalence of prediabetes in Indonesia is increasing Type 2 Diabetes prevalence and its complications. Its complications is causing economic burden since one third of the costs of Indonesia national health insurance’s claim. Based on this problem, prediabetes is the right strategy to do but in practice it is an effective and efficient method for high-risk groups, namely obesity. The current assessment is the Body Mass Index (BMI) but has limitation for those with big muscle . Waist circumference is debated. Similarly, waist to height ratio is shown to have corellation to prediabetes. But, studies that explain which are the best anthropometry indicator that have strongest corellation to prediabetes is still limited. This study aims to determine the greatest association among these anthropometry indicators to predict prediabetes in the obese group. Methods: The study used a cross sectional study design for 166 adult respondents 21-65 years who met one of the criteria for obesity: BMI> 25 kg / m2; waist circumference> 80 cm in women or> 90 cm in men; weight to height ratio 0,5. Respondents had fasting for 8-10 hours before checking sugar with a glucometer. Analysis using SPSS 18.00 program, univariate analysis to describe characteristic respondents in the Pejagalan area, then performed linear regression analysis to see the difference between BMI, waist circumference, or the waist to height ratio with most related to prediabetes. Results: The prevalence of prediabetes in obesity was 81 people (48.2%). Different age, BMI, and behavior in male and female respondents. Regression analysis showed that weight-to-height ratio is has strongest corellation in increasing risk of prediabetes. Conclusion: Waist to heigt ratio can be a measure of nutritional anthropometry that is most associated with prediabetes. Keywords: BMI, waist circumference, waist circumference - height, prediabetes